ANALISIS KEUNTUNGAN FINANSIAL USAHA PENGGEMUKAN SAPI POTONG DI KABUPATEN BOJONEGORO - Retna D Lestari; Lukman M Baga; Rita Nurmalina (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Cattle  farm  agribusiness  in  Indonesia  is  still  a  sector  that  needs  to  be developed,  given  the  increasing  demand  for  meat,  but  has  not  met  from  domestic meat  production.  One  of  the  efforts  to  achieve  stability  availability  of  beef  that  is through  an  increase  in  beef  cattle  fattening  which  have  long-term  prospects.  This study  aims  to  identify  and  analyze  the  financial  benefits  fattening  beef  cattle  in Bojonegoro  which  is  one  of  the  central  areas  of  the  cow  kind  Peranakan  Ongole (PO)  in  the  province  of  East  Java.  Data  were  analyzed  quantitatively  by  using indicators  of  profitability  and  feasibility  ie  B  /  C  Ratio,  Break  Even  Point,  Net Present Value, Internal Rate of Return, and Payback Period. The research location in  the  village  Napis,  District  Tambakrejo  with  30  respondents  breeders  who  do fattening for 4 months. The results showed the average value of B / C ratio of 1.23, NPV of USD 481 110, 59, IRR 11.30%, and PBP for 2 years and 9 months. Based on the research results can be suggested to the Government of Bojonegoro in order to provide  guidance  and  directs  farmers  to  conduct  fattening  cattle  given  the  small number of farmers who cultivate the cow on a large scale.